2020
DOI: 10.1002/jcla.23392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of COVID‐19 convalescent patients with re‐positive nucleic acid detection

Abstract: Hui and Fu contributed equally to the work.Ye and Cai contributed equally to the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 14 publications
(20 reference statements)
2
76
0
Order By: Relevance
“…Chung et al 13 reported that 76% of the patients had bilateral lung affection, and also, 76% had their lower right lobe involved. Zhu et al 14 revealed that slow absorption of lung lesions in patients may be associated with persistent positive RT‐PCR test results. We found in Group S a higher proportion of bilateral lung lobe infections, which implies more serious infections in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Chung et al 13 reported that 76% of the patients had bilateral lung affection, and also, 76% had their lower right lobe involved. Zhu et al 14 revealed that slow absorption of lung lesions in patients may be associated with persistent positive RT‐PCR test results. We found in Group S a higher proportion of bilateral lung lobe infections, which implies more serious infections in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Different countries may make slightly different discharge criteria based on their context. The chest CT of one case presented recurrent symptoms with blurred image in the upper lobe of both lungs, more prominent on the left side during the convalescent period, but the severity of image is less than that of late period of hospitalization [108][109][110][111][112][113][114].…”
Section: Discharge Managementmentioning
confidence: 92%
“…Reinfections have been reported with other human coronaviruses, namely, 229E, NL63, OC43, all of which generally cause milder respiratory illness. Hitherto, multiple cases of clinical recurrence of COVID-19 and/or positive real time-polymerase chain reaction (RT-PCR) results after recovery have been reported [ [3] , [4] , [5] , [6] , [7] , [8] ]. Among 576 patients with COVID-19 discharged from hospital in Chongqing, China, 61 patients (10.6%) had positive RT-PCR test results [ 6 ].…”
mentioning
confidence: 99%
“…Zhou et al has reported that COVID-19 patients who “relapse” after discharge are usually elderly, have poor immune function, and have more comorbidities [ 36 ]. Accordingly, multiple cases of clinical recurrences of COVID-19 and/or re-positives of SARS-CoV-2 RT-PCR have been reported in patients with DM [ [3] , [4] , [5] , [6] , [7] , [8] ]. Amongst 61 patients who had turned re-positive after being discharged from the hospital, 5 had DM [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation